Predictive power of confidence indicators for the Russian economy - Niko Korte (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
This study examines the forecasting power of confidence indicators for the Russian econ-omy. ARX models are fitted to the six confidence or composite indicators, which were then compared to a simple benchmark AR-model. The study used the output of the five main branches as the reference series. Empirical evidence suggests that confidence indica-tors do have forecasting power. The power is strongly influenced by the way which the in-dicator is constructed from the component series. The HSBC Purchasing Managers' Index (PMI), the OECD Composite Leading Indicator (CLI) and the OECD Business Confidence Indicator (BCI) were the best performers in terms of both the information criterion and forecasting accuracy.
URN:NBN:fi:bof-201408072152
Keywords: E37; P27; 330; confidence indicators; forecasting; Russia